Anestesia epidural com alfa 2-agonistas e lidocaína para realização de ovariossalpingohisterectomia em cadelas - Pohl, Virgínia Heinze (2010)
This study objective to determine the cardiorrespiratory effects and viability of the association between various alpha2-agonists and lidocaine via epidural in bitches submitted to ovaryhysterectomy. Fourty two bitches were castrated under lumbo-sacral epidural anesthesia with lidocaine 1% with vasoconstrictor (CON) or associated with 0,25 mg/kg of xylazine (XYL), 2 mg/kg of dexmedetomidine (DEX), 5 mg/kg of clonidine (CLO), 10 mg/kg of romifidine (ROM), or 30 mg/kg of detomidine (DET), with a total volume of 1ml/4kg. During the procedure, cardiac (HR) and respiratory (RR) rates, and systolic, mean and dyastolic arterial pressures were measured before epidural and every 10 minutes after the epidural injection. Also pH and blood gases were measured before, 30 and 60 minutes after epidural injection. If the animals presented disconfort signals, they were submitted to inhalatory anesthesia with isoflurane 5%, intubated and manteined with 1,5% ETiso. The duration of epidural block and pos-operatory analgesia were also measured. All animals in CON and DEX groups, five animals in ROM and CLO, four animals in XYL and three animals in DET needed complementation with inhalatory anesthesia. All groups, except CLO, presented decrease in HR. There was increase in blood pressures, and DET presented marked hypertesion.Values of RR, blood gases and duration of epidural block were similar between groups. Post-operatory analgesia was prolonged in XYL, persisting for up to four hours. None of the protocols tested was totally efficient, but xylazine prolonged post-operatory analgesia. The second chapter of this dissertation aimed to evaluate the correlation between visual analog scale (VAS), Melbourne pain scale and Von Frey filaments in the evaluation of postoperatory pain in bitches submitted to ovaryhysterectomy. The same animals were evaluated by two observers unaware of the protocol used, in one-hour intervals, using VAS, Melbourne pain scale and Von Frey filaments, applied around the surgical wound. A score of 50 mm in VAS or 13 points in the Melbourne pain scale were considered as the criterion for analgesic administration. VAS and Melbourne pain scale showed a good correlation, with r = 0,74. Correlation between EVA and Von Frey filaments was weak (r = -0,40). Correlation between Melbourne pain scale and Von Frey filaments was -0,37. VAS revealed to be the most sensitive scale. VAS and Melbourne pain scale determined a good correlation degree. We sugest a lower score in the Melbourne pain scale to be considered as criterion for analgesic administration.